DISSOCIATION IN TMDs/HEADACHE/, TMDs/NON HEADACHE, AND NON TMDs/NON HEADACHE CONTROLS: HEALTH IMPLICATIONS IN THE GENERAL POPULATION - Molina Tinoco; Zeila Coelho Santos; Bruno Ricardo Huber Simião; Raphael Navarro Aquilino; Douglas Oliveira de Andrade; Rise Consolação Iuata Rank; Rogério Ferreira Marquezan (REVISTA CEREUS, 2014)
Goal:Evaluate scores in dissociation in TMD and non TMD individuals. Methods:The Dissociative Experience Scale or DES was used  in 196 TMDs and Headache, 39 TMDs no headache, 75 controls with headache and 38 controls with no headache individuals. Clinical examination, palpation of joint/muscles, criteria for TMDs and for differente headache types were used. Results: Mean DES scores  in the TMD+HA, TMD - HA, Controls, Controls +HA and Controls - HA  were about 17,7, 22,0  12, 6, 14, 8 and 10,5 respectively ( Tukey-Kramer ANOVA p<0.0001). The frequency of severe dissociation  increased from the control  no headache  to the control + headache, to the TMD - headache and  and to the TMD+headache subgroups (X-square for independence p=0,03, X-square for trends p=0,02).  Conclusion: Higher scores in dissociation were observed in the subgroups presenting TMDs with and without headache. Controls  no TMDs with headache presented higher scores as compared to Controls no TMDs amd mp headache. Headache in both TMDs and control individuals may increase the likelyhood of presenting higher scores in dissociation.Keywords: Dissociation. TMDs. Headaches.